Effect of caries-affected dentin on one-step universal and multi-step etch-and-rinse adhesives' bond strength - Clecila MÜLLER; Gabriela Cauduro da ROSA; Gabriela Simões TEIXEIRA; Ivo KREJCI; Tissiana BORTOLOTTO; Alexandre Henrique SUSIN (Universidade Estadual Paulista, 2017)
Abstract Objective To evaluate the influence of caries-affected dentin on bond strength of a universal one-step and a multi-step etch-and-rinse adhesive system. Material and method Enamel of 60 third human molars with and without caries was removed to expose dentin. The teeth were randomly assigned to six groups: Single Bond Universal (3M ESPE, St. Paul, MN, USA) in etch-and-rinse and in self-etch mode and Prime & Bond NT (Dentsply Co, Konstanz, Germany), all on sound and caries-affected dentin. Smear layer of the 30 sound dentin specimens was standardized by polishing with 600-grit SiC paper under water cooling. Residual infected dentin of the 30 caries-affected specimens was removed with a number 4 CA carbide bur until no caries smooth tissue was detectable by tactile-visual inspection. Cylinders of a light cured composite resin (Filtek Z350 XT, 3M ESPE) were built up using starch tubes and microshear test was performed until failure. The data was analyzed by one-way ANOVA and Tukey's post hoc test. Result Significant differences in microshear bond strength (μSBS) were observed for the caries-affected groups, but not for sound dentin. The μSBS of Single Bond Universal were not influenced by the application protocol on sound dentin, however they were lower in the caries-affected group with both application protocols. The μSBS for Prime & Bond NT was not influenced by the dentin conditions. Conclusion Caries-affected dentin decrease in bond strength of Single Bond Universal in comparison to sound dentin. The bond strength of Prime & Bond NT was not altered by substrate conditions.